Multifocal Pancreatic Ductal Adenocarcinomas Concomitant with Intraductal Papillary Mucinous Neoplasms of the Pancreas Detected by Intraoperative Pancreatic Juice Cytology. A Case Report - Mori, Yasuhisa; Ohtsuka, Takao; Tsutsumi, Kosuke; Yasui, Takaharu; Sadakari, Yoshihiko; Ueda, Junji; Takahata, Shunichi; Nakamura, Masafumi; Tanaka, Masao (JOP. Journal of the Pancreas, 2010)
Context Intraductal papillary mucinous neoplasms (IPMNs) of the pancreas have been detected with increasing frequency as a result of the progression of diagnostic modalities. Recently, invasive ductal carcinoma of the pancreas concomitant with IPMNs has been the focus of attention. Case report We report the case of a 57-year-old man with multifocal ductal carcinomas of the pancreas concomitant with IPMNs detected by intraoperative cytology. During a follow-up for branch duct IPMNs, a stenotic lesion of the main duct in the pancreatic body was found by ERCP, and brush cytology of the stenosis revealed an adenocarcinoma. A distal pancreatectomy was proposed; however, intraoperative pancreatic juice cytology from the pancreatic head also revealed adenocarcinoma, and a total pancreatectomy was finally carried out. Pathological examination of the resected specimen showed multifocal ductal carcinomas and IPMNs in the distal pancreas, and invasive ductal carcinoma in the pancreatic head which had not been detected by preoperative imaging studies. Conclusions Surgeons should be aware of the possibility of multifocal carcinomas in patients with concomitant IPMNs. Intraoperative pancreatic juice cytology should always be performed in order to confirm the absence of carcinoma in the pancreas to be left in place after planned resection. Image: Schematic representation of the location of IPMNs and non-invasive and invasive ductal carcinomas.